Nemo (2013), volume 3 ebook River of ghosts. - Moore, Alan (The League of Extraordinary Gentlemen: Nemo, 2015)
In a world where all the fictions ever written coalesce into a rich mosaic, it's 1975. Janni Dakkar, pirate queen of Lincoln Island and head of the fabled Nemo family, is eighty years old and beginning to display a tenuous grasp on reality. Pursuing shadows from her past—or her imagination—she embarks on what may be a final voyage down the vastness of the Amazon, a last attempt to put to rest the blood-drenched spectres of old. With allies and adversaries old and new, we accompany an ageing predator on her obsessive trek into the cultural landscape of a strange new continent, from the ruined city of Yu-Atlanchi to the fabulous plateau of Maple White Land. As the dark threads in her narrative are drawn into an inescapable web, Captain Nemo leads her hearse-black Nautilus in a desperate raid on horrors believed dead for decades.